2016
DOI: 10.1007/s10450-015-9755-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, surface characterization and electrokinetic properties of colloidal silica nanoparticles with magnetic core

Abstract: In order to obtain functionalized silica colloids with magnetic properties, the three-step reaction, was carried out. The aqueous suspension of iron oxide nanoparticles as magnetic core (maghemite-c-Fe 2 O 3 ) was synthesized according to the Massart's method (Massart in IEEE Trans Magn 17:1247-1248, 1981. A silica shell was obtained onto maghemite employing a modified sol-gel method by Salgueirino (Salgueirino-Maceira et al. in Adv Mater 19:4131-4144, 2006). As-synthesized magnetic silica core/shell nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…NaOH and HNO 3 were employed to adjust the pH values of the suspensions. In order to determine the zeta potential, three equations were used: Huckel’s, Henry’s and Smoluchowski’s (Gdula et al., 2016). The previous experiments have shown that in any case κ·a relation was higher than 100.…”
Section: Methodsmentioning
confidence: 99%
“…NaOH and HNO 3 were employed to adjust the pH values of the suspensions. In order to determine the zeta potential, three equations were used: Huckel’s, Henry’s and Smoluchowski’s (Gdula et al., 2016). The previous experiments have shown that in any case κ·a relation was higher than 100.…”
Section: Methodsmentioning
confidence: 99%
“…The shell contributes to the improvement of their chemical and physical properties and ensures increased biocompatibility and biodegradability. Silica is the most widely used to functionalize the surface of nanoparticles [2], because it provides a steric barrier against core agglomeration preventing interactions between nanoparticles [3,4], good hydrophilicity (due to Si-OH), an increase in the stability of the dispersions over a wide pH range, and biocompatibility of the nanoparticles; it also allows the attachment of other functional groups for further application [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles used for the diagnosis should be free of agglomerates, be super-magnetic at room temperature, and be biocompatible and nontoxic. [22]. Therefore, it is necessary to enhance the synthesis method to improve the physicochemical properties of magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%